2006
DOI: 10.1200/jco.2006.06.6100
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Genetic Testing and Assisted Reproduction

Abstract: While constituting new reproductive options for families affected by cancer, the medical indications and ethical acceptance of assisted reproductive technologies for adult-onset cancer predisposition syndromes remain to be defined. Continued discussion of the role of PGD in the reproductive setting is needed to inform the responsible use of these technologies to decrease the burden of heritable cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 68 publications
0
57
0
1
Order By: Relevance
“…22 PGD for cancer predisposition divides opinion among health professionals in Europe 17,23 and the United States. 24,25 Attitudes among people at risk of cancer towards PGD are similarly mixed. [26][27][28] However, all of these studies have been conducted with women of all age groups -for the majority of respondents, age may preclude having (further) children, and some studies include women who do not have a BRCA mutation and so would not be able to use PGD.…”
Section: Introductionmentioning
confidence: 95%
“…22 PGD for cancer predisposition divides opinion among health professionals in Europe 17,23 and the United States. 24,25 Attitudes among people at risk of cancer towards PGD are similarly mixed. [26][27][28] However, all of these studies have been conducted with women of all age groups -for the majority of respondents, age may preclude having (further) children, and some studies include women who do not have a BRCA mutation and so would not be able to use PGD.…”
Section: Introductionmentioning
confidence: 95%
“…PGD for hereditary cancer is particularly controversial and is still not widely used. [4][5][6][7] Lavery et al 8 found that PGD users (for diseases other than FAP) and who also had experience with PND reported that the experience of PND followed by termination had a negative impact and that PGD is a potentially valuable alternative. Although the first PGD procedures for FAP were already performed in 1998, 3 the availability of both PND and PGD for FAP still varies between countries.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,14 More recently, PGD has been used to detect cancer predisposition, including BRCA mutations. 6,17 The first case report of an Australian baby born after PGD for a BRCA1 mutation was published in 2008. 15 In a following report of a case series of 10 women seeking consultation about PGD for a BRCA mutations in Israel, five underwent the procedure, which resulted in three pregnancies with three live births (a set of twins and a singleton; the third pregnancy was ongoing).…”
mentioning
confidence: 99%